2017
DOI: 10.1111/ejn.13759
|View full text |Cite
|
Sign up to set email alerts
|

Mnemonic and attentional roles for states of attenuated alpha oscillations in perceptual working memory: a review

Abstract: Alpha oscillations are often reported to be amplified during working memory (WM) retention, serving to disengage sensory areas to protect internal representations from external interference. At the same time, contemporary views of WM postulate that sensory areas may often also be recruited for retention. I here review recent evidence that during such ‘perceptual’ WM, alpha oscillations in mnemonically relevant sensory areas are not amplified but attenuated instead. I will argue that such attenuated alpha state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
79
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 98 publications
17
79
2
Order By: Relevance
“…Overall our study supports the important role of circumscribed alpha decreases in prioritizing relevant information in working memory (van Ede, 2018).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall our study supports the important role of circumscribed alpha decreases in prioritizing relevant information in working memory (van Ede, 2018).…”
Section: Introductionsupporting
confidence: 84%
“…While this load dependent top-down amplification of alpha is widely accepted, also circumscribed decreases in alpha power (often labeled as desynchronization) have been deemed functionally important in the context of working memory tasks, reflecting an enhanced activation of performance-relevant neural ensembles (e.g. (Noh et al, 2014;Sauseng et al, 2009); see (van Ede, 2018) for review). A recent framework by Hanslmayr et al aiming at explaining the role of neural oscillations underlying episodic memory (Hanslmayr et al, 2016) explicitly links the extent of alpha desynchronization to the representational strength of the information content.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, results from the cluster-based permutation tests are in conflict with 335 previous studies reporting scaling of alpha amplitude with working memory on an 336 across subject level [21,22,24,50]. Instead, the present study identified high 337 inter-individual variability of alpha amplitude and topography.…”
contrasting
confidence: 87%
“…Apart from the alpha-band, theta-band power modulations are commonly reported 358 in the study of working memory load [21,24,33] and are hypothesized to play a crucial 359 role in organizing sequential information [22,24]. In the present study, decoding models 360 for most subjects did not rely on theta, with the exception of subject #4.…”
mentioning
confidence: 65%
See 1 more Smart Citation